ANALISIS STUDI KELAYAKAN USAHA DENGAN KEUANGAN DAN PEMASARAN (STUDI KASUS YELLOW BIKE COFFEE) - Nadya Arista; Dyah Puspitasari Sunaryo Putri (Universitas Pamulang, 2022)
Yellow Bike Coffee is a cafe business that has been running since 2018 and starting in 2019 this business began to experience a decrease in revenue. This study aims to analyze the causes of the decline in income through business feasibility analysis in terms of financial and marketing aspects, so as to produce recommendations for corrective actions to increase sales. The methodology used is qualitative research. The results of financial analysis research using the Payback Period (PP) method within 5 years the total cash flow is 43,218,247, -, this means that it still cannot cover the investment of Rp. 43,552,000, - , the Net Present Value (NPV) is - Rp 8.950.343, Profitability Index (PI) is 0.79, Benefit Cost Ratio (BCR) is 1 %. As for the marketing analysis based on STP and 4P tools, Yellow Bike Coffee has unfavorable results, especially on product, price, place and promotion..